Pulled in and pushed out of politics: The impact of neoliberalism on young people's differing political consumerist motivations in the UK and Greece. Issue 2 (March 2022) - Kyroglou, Georgios; Henn, Matt
Political consumerism refers to citizens' use of boycotting and buycotting as they seek to influence political outcomes within the marketplace rather than through more traditional routes such as voting. However, given the pressure that neoliberalist forces exert on the marketplace, the lack of literature problematising the relationship between political consumerism and neoliberalism is somewhat surprising. Addressing this gap, we examine how neoliberalism impacts youth political consumerism in the UK and Greece. Focus-group findings suggest the existence of two inter-connected effects. Firstly, we detect a neoliberal 'push effect' away from electoral politics. Secondly, we discern a parallel 'pull effect' as young people seek the 'political' within the marketplace. In Greece, youth political consumerism seems to result primarily from distrust of institutional political actors. In contrast, young political consumers in the UK appear to be principally driven by confidence in the capacity of the market to respond to their pressing needs.